Geotechnical Properties Of Adapazari Silt - AREL, ERSİN; ÖNALP, AKIN (Springer Heidelberg, Tiergartenstrasse 17, D-69121 Heidelberg, Germany, 2012)
The geotechnical properties of silts have not been investigated extensively, because they are not found in every soil environment. It is even more difficult to understand the behaviour of silts when they are encountered in appreciable volumes. It has recently been claimed that such fine-grained soils have a potential for liquefaction, similar to sands a fact that was confirmed during the 1999 Marmara earthquake in Turkey. This paper provides a basis for explaining the unique behaviour of silts in seismic conditions by investigating their physical and mechanical features. The results are ultimately expected to provide a satisfactory answer to the as yet unexplained issue of how silts behave during earthquakes.
Keywords: Silt; Fluvial deposits; Physical properties; Compressibility; Dynamic behaviour; Shear strength; strength; alüvyon; akarsu çökelleri; Fiziki ozellikleri; Sıkıştırılabilme; dinamik davranış; kayma mukavemeti; kuvvet